Pengaruh Direct Method terhadap Penguasaan Kosakata Bahasa Arab Siswa Kelas VI di Madrasah Ibtidaiyah - Muhammad Roh Madani; Elhefni Elhefni; Djoko Rohadi Wibowo; Ahmad Syarifuddin (Limas PGMI, 2022)
This study aims to: (1) To find out how the Arabic vocabulary mastery of class VI students at MI Nurul Falah Air Mesu Timur before using the direct method. (2) To find out how the Arabic vocabulary mastery of class VI students at MI Nurul Falah Air Mesu Timur after using the direct method. (3) To determine the effect of the direct method on Arabic vocabulary mastery of sixth grade students at MI Nurul Falah Air Mesu Timur. The type of research used is quantitative, namely the influence of the direct method on students' Arabic vocabulary mastery. The test subjects in this study were class VI students of MI Nurul Falah Air Mesu Timur. Based on the results of the research conducted, it can be concluded that the effect of the direct method on students' Arabic vocabulary mastery shows that the results of Ho are rejected and Ha is accepted with the results of the hypothesis test that the value of sig(2-tailed) = 0.000. Because the significant value is less than 0.05 which means that there is a direct method effect on Arabic vocabulary mastery of sixth grade students at MI Nurul Falah Air Mesu Timur. The significant effect of using the direct method on students' Arabic vocabulary mastery is increasing students' Arabic vocabulary mastery. Likewise, without the use of the direct method, the students' Arabic vocabulary mastery is relatively small.